Penguatan Literasi Ekonomi dan Kewirausahaan Anak Pekerja Migran Indonesia Berbasis Participatory Learning di Kampung Melayu Sungai Buloh, Malaysia - Hidayati, Nur; Luayyi, Sri; Umam, Ahmada Khoirul; Nurrahma, Avinta Ika; Yani, Ahmad (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The International KKN program organized by the Islamic University of Kadiri (UNISKA) Kediri was implemented through community service activities focusing on socialization and entrepreneurial literacy for 69 elementary school children in Kampung Melayu Sungai Buloh, Malaysia. The program aimed to increase learning motivation, entrepreneurial enthusiasm, and to develop the creativity and independence of migrant children. It applied a Participatory Learning approach that actively involved students through three stages: planning, implementation, and evaluation. The results indicate that entrepreneurial literacy is an effective strategy for fostering creativity and independence among children of migrant workers. Through workshops, business simulations, and literacy-based activities, participants were able to generate creative ideas, manage simple business projects, build self-confidence, enhance adaptability, and demonstrate positive growth in social, emotional, and basic economic skills, preparing them for a more independent future.